Cognitive Mechanisms Of Kazakhstan Commercial And Social Advertising Text - Nurbayeva, Aida; Gulzhan Kalambayeva, Bakitkul Tansykbayeva, Gulshara Kunakova, Lelya Bugenova, (Opción, 2019)
The aim of the study is to investigate Cognitive mechanisms of Kazakhstan commercial and social advertising text via theoretical studies of modern scientists-cognitivists and slogans from the practice of Kazakhstan commercial and social advertising, which have, as it turned out, the similar cognitive characteristics. As a result, drug addiction leads to the destruction of the nervous system, physical health, and, finally, to death. In conclusion, the most effective advertising today is a kind of viewing device in which the viewer is involved due to mixing and compressing information